Tax and the city: A theory of local tax competition and evidence for Germany - Eckhard Janeba; Steffen Osterloh (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
Despite the well-developed empirical literature on local tax competition, little is known about the actual spatial structure of inter-municipal competition. Assuming that competition takes place only among neighbours (as in the empirical literature) is at odds with the theoretical approaches where all jurisdictions compete simultaneously. In this paper we use a survey conducted among mayors in the German state of Baden-Württemberg to show that the perceived intensity of competition for firms varies considerably between jurisdictions and can mainly be explained by the size and location of the jurisdiction. Based on these findings, we develop a sequential tax competition model in which urban centres compete with other urban centres and rural jurisdictions in their own neighbourhood. This model predicts that larger jurisdictions do not necessarily rely more on capital taxes; in case they face strong competition with more distant competitors, larger cities even have lower capital taxes. In addition, we discuss how the model compares to a standard simultaneous approach and show that results from our sequential model are in line with trends in local taxation in Baden-Württemberg.
Keywords: H71; H73; H77; 330; local tax competition; survey; intensity of competition; asymmetric tax competition